2009
DOI: 10.1021/jm900909e
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spirocyclic 3-(3-Fluoropropyl)-2-benzofurans as σ1 Receptor Ligands for Neuroimaging with Positron Emission Tomography

Abstract: A series of various N-substituted 3-(3-fluoropropyl)-3H-spiro[[2]benzofuran-1,4'-piperidines] (7) has been synthesized. In receptor binding studies, the N-benzyl derivative 7a (WMS-1813) revealed extraordinarily high sigma(1) receptor affinity (K(i) = 1.4 nM) and excellent sigma(1)/sigma(2) selectivity (>600 fold). In vitro biotransformation of 7a with rat liver microsomes led to three main metabolites. N-Debenzylation was inhibited by introduction of an N-phenylethyl residue (7 g). The PET tracer [(18)F]7a wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 52 publications
1
62
0
Order By: Relevance
“…Organ distribution studies in mice using the corresponding fluorine-18-labeled radiotracer [ 18 F]1 demonstrated that this class of derivatives offers excellent potential for neuroimaging of central s 1 receptors with PET. [40] Next, we investigated the effects of replacing the 3-fluoropropyl moiety of 1 with a 2-fluoroethyl residue. This structural modification resulted in the more potent and selective ligand 2 (K i (s 1 ) = 0.59 nm; K i (s 2 ) = 785 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Organ distribution studies in mice using the corresponding fluorine-18-labeled radiotracer [ 18 F]1 demonstrated that this class of derivatives offers excellent potential for neuroimaging of central s 1 receptors with PET. [40] Next, we investigated the effects of replacing the 3-fluoropropyl moiety of 1 with a 2-fluoroethyl residue. This structural modification resulted in the more potent and selective ligand 2 (K i (s 1 ) = 0.59 nm; K i (s 2 ) = 785 nm).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently synthesized 4 series of spirocyclic benzofurans (11)(12)(13)(14) and selected 4 derivatives (K i 5 0.59-1.4 nM) for 18 F labeling and evaluation as PET tracers (13)(14)(15)(16). Although all appear to be applicable for neuroimaging of s 1 Rs, a 2-fluoroethyl homolog, named 18 F-fluspidine, was most suitable (2).…”
mentioning
confidence: 99%
“…However, structural modifi cation was needed to introduce fl uorine in a suitable labeling position. Accordingly, various series of derivatives have been synthetized to select those with the highest affinity, selectivity, and in vitro metabolic stability [133][134][135][136][137][138] .…”
Section: New Compoundsmentioning
confidence: 99%